Large-scale surveys of woodrats ( Neotoma spp.) reveal constraints on diet breadth in herbivorous mammals - Sara B. Weinstein; Dylan M. Klure; Efthymia Symeonidi; Robert Greenhalgh; Marc T. Mayes; Margaret L. Doolin; Tess E. Stapleton; Andrea Swei; Michael V. Cove; M. Denise Dearing (Proceedings of the National Academy of Sciences, 2025)
Characterizing niche space is critical for predicting species interactions and responses to environmental change. To enhance our understanding of dietary niche breadth, we used DNA metabarcoding to examine how diets of a widespread, model herbivore (woodrats, genus Neotoma ) respond to changing resources and the extent to which dietary specialization is conserved across space and time. We used diet data from 13 species, 57 populations, and over 500 individuals to examine predictors of niche breadth and interindividual diet variation at a landscape scale. Then, to test whether these patterns are conserved across scales, we explored the same questions using a single population sampled over 5 y and mark-recapture data from individuals sampled at least three times. We found that woodrats exhibited a continuum of dietary specialization that included species-level dietary generalists and specialists. Specialist species maintained narrow population-level niche breadths with little evidence of interindividual diet variation. In contrast, generalist species consisted of populations with varying degrees of dietary specialization and interindividual diet variation. Across sampling scales, increased population-level niche breadth was explained by both increased interindividual diet variation and increased diet richness. These results are consistent with the Niche Variation Hypothesis and suggest that diet breadth is constrained by costs of both specialization and generalization.